Pemikiran Filosofi Ali Syari'ati - Ernita Dewi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Ali syari‟ati is an Islamic scholar and altogether a pioneer who opposed  tyranny manfully. Living in the crisis country that practiced nepotism, make him  realized about the important humanities in the creation a clean governance that up  holds Al-Quran and Sunnah. Philosophical studies that he learned since he was a  kid until doctorate program, made him become a socialist who gave serious  attention to oppressed laymen. His brilliant thoughts suggest Muslims to be stout- hearted to fight against evilness. Although, the in discourse of philosophy of  history explains that dialect between evilness and goodness never ends until the  destruction day, a man cannot end the fight.